Brief cycling intervals incrementally increase the number of hematopoietic stem and progenitor cells in human peripheral blood - Pradana, F.; Nijjar, T.; Cox, P. A.; Morgan, P. T.; Podlogar, T.; Lucas, S. J. E.; Drayson, M. T.; Kinsella, F. A. M.; Wadley, A. J. (Frontiers in Physiology, 2024)
Introduction Peripheral blood stem cell (PBSC) donation is the primary procedure used to collect hematopoietic stem and progenitor cells (HSPCs) for hematopoietic stem cell transplantation. Single bouts of exercise transiently enrich peripheral blood with HSPCs and cytolytic natural killer cells (CD56dim), which are important in preventing post-transplant complications. To provide a rationale to investigate the utility of exercise in a PBSC donation setting (˜3 h), this study aimed to establish whether interval cycling increased peripheral blood HSPC and CD56dim concentrations to a greater degree than continuous cycling.